Adoption of AI in the Banking Industry : A Case Study on Indian Banks - Pahari, Subhajit; Polisetty, Aruna; Sharma, Soma; Jha, Rimjhim; Chakraborty, Debarun (Indian Journal of Marketing, 2023)
The Indian banking sector has been at the forefront of accepting innovative technologies and has been changing over time. Indian banks are utilizing AI-powered technologies to automate labor-intensive operations, reduce operational costs, and increase revenue growth potential. Already, machines handle a large portion of mundane tasks. In order to increase security and transparency in payment fraud detection and prevention systems, financial institutions are also utilizing artificial intelligence (AI). But in recent days, Indian banks are facing huge issues with regard to AI adoption and implementation, which needs further investigation. The present work is a case study considering two leading private banks in India. The study revealed the critical driving force of AI maturity and the key concern areas that need to be adequately addressed to ensure long-term success regarding AI adoption in the Indian banking sector.